The Silver Economy as a Constructive Response in Public Policy on Aging - Andrzej Klimczuk (Strategic Approach to Aging Population: Experiences and Challenges, 2021)
The paper presents the concept of the "silver economy" as an economic system related to population aging and underlines the features of this policy idea. The study first introduces the discourse and stages of constructing this system by international and national public policy actors in aging. Next, a critical analysis of the dimensions and areas of implementation and development of the silver economy as a policy concept was carried out as well as a review of its external and internal limitations. The conclusion contains proposals for further research directions.
Keywords: J14; J18; P49; P59; 330; aging policy; longevity economy; policy ideas and concepts; silver economy